Zaangażowanie społeczno-obywatelskie młodzieży akademickiej jako czynnik chroniący w perspektywie koncepcji resilience - Marciniak, Mateusz (Rocznik Pedagogiczny, 2019)
The paper analyses the relationship between the civic engagement and risk behaviours of young peo- ple from the perspective of resilience mechanisms. The resilience concept focuses on social and in- dividual features which protect (give the resistance) against risk factors appearing in adverse living conditions. Civic engagement is included among potential protective factors. Can this engagement can be considered as a protective factor in the context of the crisis of democracy and social capital erosion, and if so, to what extent? The goal of this paper is to analyze the civic engagement of uni- versity students as a potential protective factor against risk behaviours, in particular, alcohol abuse. Firstly, the basic assumptions of resilience and civic engagement (in social capital perspective) are defined. The second section is based on selected findings from the study Studenci 2019’ (N=4503): the associations between the degree of civic engagement of university students and alcohol-related problems. The research results show that the students from the group with a higher level of civic engagement (in comparison to those with a lack or low level) are found significantly more often among students with problems related to risk-drinking and alcohol abuse. The article ends with an explanation of thoe findings which may be considered surprising in light of the concept of resilience.